Effective treatments for paronychia caused by oncology pharmacotherapy. Issue 6 (24th November 2015) - Goto, Hiroyuki; Yoshikawa, Shusuke; Mori, Keita; Otsuka, Masaki; Omodaka, Toshikazu; Yoshimi, Kosuke; Yoshida, Yuichi; Yamamoto, Osamu; Kiyohara, Yoshio
Abstract: Cutaneous adverse events are relatively common in patients being treated with molecular‐targeted drugs. Paronychia is one of the cutaneous adverse events that influences the patient's quality of life because of pain, and it often affects anticancer treatments in severe cases. However, there are few effective treatments, especially for severe paronychia. Here, we present our experiences of treatment for paronychia due to oncology pharmacotherapy. Although we treated paronychia with various methods, only corticosteroid ointment and phenol chemical matricectomy significantly improved the paronychia. Dermatologists must perform appropriate and effective treatments for paronychia in order to enable patients to continue anticancer drug treatment without impairing their quality of life.